ChemInform Abstract: Three‐Component, One‐Pot Synthesis of Hexahydroazepino[3, 4‐b]indole (VI) and Tetrahydro‐1H‐pyrido[3, 4‐b]indole Derivatives (IV) and Evaluation of Their Cytotoxicity. Issue 9 (March 2015) - Reddy, B.V. Subba; Venkata Ganesh, A.; Vani, M.; Ramalinga Murthy, T.; Kalivendi, Shasi V; Yadav, J. S.
Abstract New compounds (IVa), (IVc), (IVe), (VIb), and (IVf) show significant cytotoxic efficacy against different cancer cell lines.